Resolution without Enforcement: A Critical Study of Case Closure and Substantive Justice in Indonesian Court Mediation - Bustanul Arifien Rusydi; Ahmad Khairun Hamrany; Tata Wijayanta; Deslaely Putranti (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2026)
This study analyses the quality standards of mediated outcomes and the safeguarding mechanisms associated with withdrawal and consent judgments under Supreme Court Regulation (Perma) No. 1 of 2016, through the lens of ṣulḥ, to offer a substantively just model of mediation. Methodologically, the research adopts a normative-conceptual approach, applying dispute system design doctrine to Indonesia’s mediation regulation. Qualitative analysis is conducted on ten sample court decisions representing post-mediation dispositions. The findings indicate that Perma No. 1 of 2016 frames mediation “success” in terms that prioritize case closure over the locking-in of enforceable commitments, thereby weakening protection for claimants in high-stakes disputes. A ṣulḥ-based procedural design is argued to support mediated settlements that are more binding, executory, and capable of deterring dispute recurrence. This study recommends that Perma No. 1 of 2016 be supplemented with a substantive initial classification mechanism requiring mediators to identify the type of dispute and its economic value, and to steer mediation toward an executory consent judgment.